2010
DOI: 10.1002/aic.12224
|View full text |Cite
|
Sign up to set email alerts
|

Molecular reconstruction of complex hydrocarbon mixtures: An application of principal component analysis

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Three methods for reconstruction of the detailed molecular composition of complex hydrocarbon mixtures, based on their global properties, are compared: a method based on the Shannon entropy criterion, an artificial neural network and a multiple linear regression model. In spite of the broad range of naphthas included in the training set, the application range of the last two methods proved to be limited. Principal component analysis allowed to identify their thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 65 publications
0
42
0
Order By: Relevance
“…In order to simulate cracking furnaces appropriately, several parameters of Coilsim1D model must be corrected based on the parameters and operating data of cracking furnace, such as the coil size and material, cracking severity [15]. After correcting, the output of cracker model is similar with the furnace output.…”
Section: Cracking Reaction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to simulate cracking furnaces appropriately, several parameters of Coilsim1D model must be corrected based on the parameters and operating data of cracking furnace, such as the coil size and material, cracking severity [15]. After correcting, the output of cracker model is similar with the furnace output.…”
Section: Cracking Reaction Modelmentioning
confidence: 99%
“…Then, the search for better producers is performed using Eqs. (13) to (15), and the location of producer is updated. Step4 A total of 80% of the other members are set as scroungers.…”
Section: Algorithm Stepsmentioning
confidence: 99%
“…However, it is impossible to get the mass yield of the whole components of cracked gas online. Considering this fact, the yield model is built based on CoilSim1D [52,53]. The input variables are the property of feedstock, COT, FLOW, SHR, and COP, and the output Fig.…”
Section: Optimization Of the Naphtha Pyrolysis Processmentioning
confidence: 99%
“…Marin et al studied on the molecular reconstruction of residual oil and naphtha with MIEM [13]. Pyl et al reported a model on molecular reconstruction of naphtha based on MIEM and made a comparison between the multiple linear regression and neural network methods [17]. Verstraete et al developed a model on molecular reconstruction of the light cycle oil fraction, Arabia light vacuum residue, and naphtha steam cracking feedstock based on MIEM [18,19].…”
Section: Introductionmentioning
confidence: 99%